EFFECT OF EXTREME HEAT ON DNA OBTAINED FROM TOOTH OF BURNT CORPSES (Journal of Forensic Medicine & Toxicology, 2021)
Determination of sex of an individual has a crucial role in personal identification. This study aims to determine the sex of an individual from burnt teeth samples exposed to a temperature of 2500C for 15 minutes and 45 minutes respectively through amplification of amelogenin marker. Independent sample t-test analysis of 60 tooth samples revealed that the mean quantity (in ìg/l) and quality of DNA were significantly reduced after heating for 15 minutes (M=9.71, SD=0.45) compared to freshly extracted tooth samples (M=29.91, SD=0.65), t(38)=114.19, p
Keywords: Amelogenin; DNA; Hydroxyapetite; Gender Identification; Electrophoresis; Forensic Investigation